2013
DOI: 10.1007/s00192-013-2094-y
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of pelvic floor muscle function in POP patients after the Prolift procedure: results from surface electromyography

Abstract: The restoration of pelvic anatomy may account for the improved PFM function with increased electrical activity in POP patients verified by SEMG. Evaluation of PFM function may be used as a clinical tool in the overall assessment of pelvic reconstructive surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A total of 5 randomized controlled trials, 14 prospective cohort studies and 2 retrospective cohort studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 5 randomized controlled trials, 14 prospective cohort studies and 2 retrospective cohort studies were included (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In eight studies, some participants had undergone previous pelvic surgery, with hysterectomy the most common procedure. Participants in six studies had not undergone any previous pelvic surgery . Only three studies reported participants’ previous experience with PFM training: in one study participants had no prior PFM training; in another study 9% had completed PFM training before participation in the study; and in the third study over 59% had done previous PFM training .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations